THE EFFECT OF COMPETENCE AND INFORMATION TECHNOLOGY ON TAX-PAYABLE SERVICES IN THE PRATAMA TAX SERVICE OFFICE JAKARTA CENGKARENG - Bambang Sutriyanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
This study aims to measure how significant the influence of employee competencies and also the use of information technology on services provided to taxpayers. In providing services to the community (in this case the tax payment service), employee competence is a determining factor for results that can have a positive or negative effect on the services provided. Supported by increasingly advanced information technology, it is expected that public services, especially to taxpayers at the Pratama Jakarta Cengkareng Tax Service Office, will be faster, easier and better than before. Keywords: Competence, Information Technology, Services